La obtención de certificación orgánica en productores cafetaleros: caso de la cooperativa CECOVASA - provincia de Inambari – Puno – Perú - Contreras Cabrera, Anggelyque Janin (2018)
This research was conducted in Inambari - Puno in the month November 2017. The objective is to identify the factors associated with obtaining an organic certification to export coffee to the United States, in the case of the Cooperativa CECOVASA. It is hypothesized that knowledge factors and limitations in certification explain the obtaining of an organic certification by coffee producers. The information was collected through structured surveys to a sample of 52 coffee producers, 46 do not use organic certification and 6 if they are certified. Based on the results of the survey, it is concluded that a greater degree of knowledge of organic agriculture, the category of producers, knowledge of agrochemicals harmful to health, measures to reduce pollution and organic certification information , they are more likely to obtain organic certification, but the limitations in organic certification as annual income, credit access, the age of the producer and the level of education, do not influence in obtaining the organic certification of Inambari.